أسباب النُّزول من منظور الحداثيين ـ عرض ونقد - دادَّه, سيرين (جامعة الوادي - University of Eloued, 2022)
الملخص: تناول هذا البحث مبحثا مهِّماً من مباحث علوم القرآن الكريم والذي له علاقة مباشرة بتفسير آياته؛ ألا وهو مبحث أسباب النُّزول القرآني. هذا الأخير استغله أصحاب الحداثة لبثِّ أفكارهم المزعومة للتَّشكيك في مُقدَّساتنا. فجاء هذا البحث ليعرض أفكارهم ويُوضِّح المَغزى منها ويُبيِّن المفاهيم التي اِدَّعوها لإثبات ما يرمون إليه، مع نقدها ودحضها بالحُجَّة الدَّامغة والبرهان الواضح. Abstract: This research dealt with an important topic of the study of the sciences of the Holy Quran, which is directly related to the interpretation of the verses of the Qur'an; namely, the study of the causes of the Qur'anic descent. The latter has been exploited by modernists to broadcast their alleged ideas to question our sanctities. This research presents their ideas and clarifies the meaning of them, as well as shows the concepts that they call to prove while criticizing and refuting them with a clear argument and clear proof.
مقال
Keywords: أسباب النُّزول؛ أصحاب الحداثة؛ شبهات حول أسباب النُّزول